Perspectives of Nagorno Karabakh conflict settlement process after the September 2022 - Poghosyan, Benyamin (National interest, 2023)
The article analyzes the current stage of the Nagorno Karabakh conflict after the September 2022 attack of Azerbaijan against Armenia. It argues that after the 2020 Nagorno Karabakh war, which ended with the trilateral Russia – Armenia – Azerbaijan statement of November 10, 2020, Azerbaijan launched a coercive diplomacy strategy, using the military escalation as the main tool for force Armenia to accept Azerbaijani vision of the future of Nagorno Karabakh and bilateral relations. Meanwhile, the start of the war in Ukraine in February 2022 resulted in weakening of Russian positions in the region, which started to lose the monopoly over the conflict settlement process. Currently Armenia – Azerbaijan negotiations are underway in three platforms, Moscow, Brussels, and Washington, which brings additional complexity to the situation, as Nagorno Karabakh conflict becomes a part of the greater Russia – West confrontation.